2016
DOI: 10.1016/j.ceramint.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element study of residual thermal stresses in veneered Y-TZP structures

Abstract: The main complications of zirconia-based laminated systems are chipping and delamination of veneering porcelain, which has been found to be directly associated with the development of residual thermal stresses in the porcelain layer. This study investigates the effects of cooling rate and specimen geometry on the residual stress states in porcelain-veneered zirconia structures. Bilayers of three different shapes (bars, semi-cylindrical shells, and arch-cubic structures) with 1.5 mm and 0.7 mm thickness of dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
5
13
0
1
Order By: Relevance
“…The authors also observed that the fast cooling (furnace opening at 800˚C -aboveT g ) led to high levels of transient tensions, which were associated to internal microcracks and, consequently, early failures. Moreover, previous studies have observed distinct residual stresses in curved areas of PVZ crowns, [41][42][43] especially when fast cooling was applied. 43 Thus, it is plausible that the difference in residual stress distributions due to different geometries and thicknesses led to the contradictory meta-analyses results regarding flexural strength and critical load to failure.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The authors also observed that the fast cooling (furnace opening at 800˚C -aboveT g ) led to high levels of transient tensions, which were associated to internal microcracks and, consequently, early failures. Moreover, previous studies have observed distinct residual stresses in curved areas of PVZ crowns, [41][42][43] especially when fast cooling was applied. 43 Thus, it is plausible that the difference in residual stress distributions due to different geometries and thicknesses led to the contradictory meta-analyses results regarding flexural strength and critical load to failure.…”
Section: Discussionmentioning
confidence: 92%
“…Finite element analysis (FEA) studies reported that cooling down restorations from 50˚C below T g is enough to decrease residual stresses and avoid thermal gradients; 42 and that an overextended cooling protocol (closed furnace until 25˚C at 2˚C/min), besides time consuming, added more tensile and compressive residual stresses throughout the porcelain layer, compared to a more reasonable slow cooling regimen (closed furnace until 450˚C). 41 Our two meta-analyses comparing fast cooling from above T g versus slow cooling, for flexural strength (Fig. 2) and critical load to failure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, when cracks in the porcelain veneer reach the veneer/core interface, they tend to graze along the interface before deflecting back into the porcelain veneer rather than penetrate the stiffer and tougher zirconia core [4,7]. This type of failure is motivated by the low interfacial fracture energy G C of PFZ [8,9] as well as presence of deleterious residual tensile stresses, formed during the veneer firing or glaze firing process due to mismatch in thermal expansion coefficients between veneer and core and low thermal diffusivities characterizing both porcelain and zirconia [1016]. The weak delamination resistance of the P/Z interface is generally attributed to the chemical inertness of the zirconia phase.…”
Section: Introductionmentioning
confidence: 99%